Green adsorbents for water remediation: Removal of Cr(vi) and Ni(ii) using Prosopis glandulosa sawdust and biochar - Salman Syed Muhammad; Razzaq Safina; Adnan Muhammad; Rozina; Sultana Sabiha; Kamal Asif; Al-Ghamdi Abdullah Ahmed; Al Farraj Dunia Abdel Aziz; Zaman Wajid (Green Processing and Synthesis)
Potentially toxic elements like Cr+6 and Ni+2 cause severe health hazards. Therefore, the current work was aimed at cleaning water using Prosopis glandulosa raw sawdust (SD) and its derived biochar (AC). Both the adsorbents were characterized via SEM, FTIR spectroscopy, EDX, and TGA and were applied for the effective removal of Ni(ii) and Cr(vi) at optimum values of experimental conditions, and the mechanism was assessed via adsorption isotherm and kinetic models. The correlation coefficient R 2 confirmed pseudo-second-order kinetics and preferred Freundlich isotherm model. Maximum removal of Cr(iv) was obtained at a pH of 4.0, a bio-sorbent concentration of 0.8 g·L−1, and a temperature of 50°C for 50 min with a metal concentration of 110 ppm, while maximum removal of Ni(ii) was obtained for a contact time of 70 min with a metal concentration of 130 ppm in the above-mentioned experimental conditions. The results of the isotherms and kinetic model revealed that metal adsorption processes involved multilayer formation on the biosorbent’s heterogeneous surface. Also, their thermodynamic investigation showed that the adsorption process is spontaneous and exothermic and, therefore, can be effectively utilized to remove Cr and Ni from water.